Factors Affecting Carbon Emission Disclosure And Its Impact On Company Financial Performance (Study Of Energy Sector Companies Listed On The IDX In 2020-2022) - Lestari, Rinda; Mukhzarudfa, Mukhzarudfa; Kusumastuti, Ratih (Jurnal Ekonomi Teknologi dan Bisnis (JETBIS), 2024)
This research aims to determine the influence of carbon performance, environmental costs, and green product innovation on carbon emission disclosure and its impact on financial performance (a case study of Energy Sector Companies Listed on the IDX in 2020-2022). The population in the research is energy sector companies listed on the BEI in 2020-2022. The research sample was selected using a purposive sampling technique, namely a sample determination technique using predetermined criteria, so that a total sample of 54 research samples was obtained. This research method uses quantitative methods. This research uses secondary data obtained through the publication of financial reports, annual reports and sustainability reports for each energy sector company listed on the Indonesia Stock Exchange (BEI). The research results show that carbon performance and green product innovation have a positive and significant effect on carbon emissions disclosure. Environmental costs have a negative but not significant effect on carbon emissions disclosure. Carbon performance has a negative and significant effect on financial performance. Environmental costs have a positive and significant effect on financial performance. Green product innovation has a negative but not significant effect on financial performance. Disclosure of carbon emissions has a positive and significant effect on financial performance. Carbon performance and green product innovation have a positive and significant effect on financial performance through carbon emission disclosure. Environmental costs have a negative but insignificant effect on financial performance through carbon emission disclosure.